An evaluation of e-learning program : A case study at institute of education development / Prof. Madya Dr Mohd Rashidee Alwi … [et.al.]. - Alwi, Mohd Rashidee; Syed Mohamad, Syed Jamal Abdul Nasir; Said, Jamaliah (2007)
This paper reveals the result of 322 distant learners' perception towards e-learning program conducted by UiTM. Generally the respondents rated above average for all aspects of distance learning program irrespective of gender, program of studies, income an occupation. Students' gender also did not show any difference in their perception. Similarly, semester of studies too, did not indicate any significant difference except their perception towards lecturer. However students' semester of studies showed significant difference towards lecturer, module and physical. Gender, income and semester of studies did not show any relationship to students' perception towards all aspects of distance learning program. However students' program of studies showed significant relationship towards their perceptions of the program. Students; CGPA showed negative relationship with all aspects of distance learning program.